ANALISIS TINGKAT EFISIENSI MOTOR LISTRIK UNTUK PENGGERAK POMPA SANDFILTER TANK AREA WATER TREATMENT PLANT STUDI KASUS: PT XYZ - Muhamad Jawas Akbar (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2022)
Water is a very important source of energy needed by living things. Water has the property of flowing from a higher place to a lower place. Therefore it is necessary to optimize using a water pump to drain water to the desired place according to needs. In general, pumps that are used to move water from one place to another are generally used by an electric motor to rotate the pump. In maintaining the optimal level, an electric motor capacity that is in accordance with the pump capacity is needed. Determination of this capacity is related to the amount of motor power required to drive the pump. With a good motor capacity, the efficiency of the pump can be increased. Based on the calculation of the total head in the piping system at the sandfilter tank pump, it is 18,708 m with a power of 5.06 kW and the working efficiency of the electric motor for the sandfilter tank is 67.46%.Keywords  : Efficiency Electric Motor, Centrifugal Pump, Water, Head Loss